Evaluation of Recombinant Dense Granule Antigen 7 (GRA7) of Toxoplasma gondii for Detection of Immunoglobulin G Antibodies and Analysis of a Major Antigenic Domain - Jacobs, Dirk (American Society for Microbiology, 1999)
Dense granule protein 7 (GRA7) of Toxoplasma gondii was expressed in Escherichia coli as a fusion protein. The leader peptide contained a 25-amino-acid mouse tumor necrosis factor fragment and six histidyl residues. After purification by metal chelate affinity chromatography, the antigen was evaluated in an enzyme-linked immunosorbent assay for detection of immunoglobulin G (IgG). For two sets of IgG-positive human serum samples, obtained from routine screening, an overall sensitivity of 81% was obtained. For chronic-phase sera, the sensitivity of detection was 79%, but chronic-phase sera with low titers were more difficult to detect (65% sensitivity for sera with immunofluorescence titer of 1/64). When GRA7 was combined with Tg34AR (rhoptry protein 2 C-terminal fragment), the sensitivity rose to 96%. For a set of acute-phase serum samples tested on GRA7, the sensitivity of detection was 94%, and high-titer IgM-positive sera were detected at an especially high rate. In contrast, when Tg34AR was used, the sensitivity was only 85% for this latter set of serum samples. Three truncated GRA7 fragments containing the same leader peptide as that of recombinant GRA7 were produced. The shortest fragment (97 N-terminal amino acids) was not reactive with human sera or with a specific anti-GRA7 monoclonal antibody, while the two larger fragments were reactive. The most important antigenic domain of GRA7 for human sera was localized between residues 97 and 146. The epitope for the specific monoclonal antibody could be further narrowed down by the use of synthetic peptides, but this epitope is not recognized by sera from T. gondii-infected humans. These results indicate that GRA7 may be considered as an additional tool for studying the immune response to T. gondii.